2020
DOI: 10.1111/jrh.12491
|View full text |Cite
|
Sign up to set email alerts
|

Urban‐Rural Disparities in Opioid Use Disorder Prevention and Response Activities: A Cross‐Sectional Analysis

Abstract: for their insights, as well as Alex Osei-Kojo and Megan Lamiotte for their assistance with data acquisition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…9 Many reported barriers to treatment are magnified in rural communities and primary care. 10,11 Clinicians, practices, and community members affiliated with the High Plains Research Network (HPRN) and the Colorado Research Network (CaReNet) identified opioid dependence as a primary concern in their communities. As the research team visited practices, clinicians and practice staff described their concerns about over-prescribing, drug diversion, potential for addiction, and the severe lack of local treatment.…”
mentioning
confidence: 99%
“…9 Many reported barriers to treatment are magnified in rural communities and primary care. 10,11 Clinicians, practices, and community members affiliated with the High Plains Research Network (HPRN) and the Colorado Research Network (CaReNet) identified opioid dependence as a primary concern in their communities. As the research team visited practices, clinicians and practice staff described their concerns about over-prescribing, drug diversion, potential for addiction, and the severe lack of local treatment.…”
mentioning
confidence: 99%
“…16 While policy reform is needed at all levels of government to expand access to MOUD and other evidence-based practices, local governments and their health departments can play an active role in opioid response implementation. 17,18 Since the opioid epidemic was declared a national emergency in 2017, about two-thirds (65%) of local health departments (LHDs) reported conducting activities to address opioid use and abuse. 19 However, the cross-jurisdictional and cross-sector scale and complexity of the opioid epidemic hinder any government or organization from adequately addressing the problem alone.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no studies of which the authors are aware have examined this relationship. Accordingly, this study adds to the broader understanding of strategies used in community opioid response, [17][18][19][20][21] particularly in rural areas. [31][32][33] That local government engagement in collaboration related to greater capacity to provide methadone but not buprenorphine 46 Public administration research has long studied "publicness" or "a characteristic of an organization which reflects the extent the organization is influenced by political authority" that will, in turn, partly determine the extent to which public values are realized.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accessibility issues are particularly pronounced in rural communities, where opioid prescribing rates are higher [2], and rates of opioid overdose death have increased dramatically [3]. While both urban and rural communities suffer from high rates of opioid prescription and overdose deaths [4], addressing OUD in rural areas is more difficult due to limited resources for prevention, treatment, and recovery [5], as well as lack of social networks and economic opportunity disadvantage [4]. Methadone has been shown to reduce the risk of opioid overdose and better aid in treatment retention compared to nonpharmacological treatments and supports alone [6].…”
mentioning
confidence: 99%